Trowels in the trenches : archaeology as social activism - Barton, Christopher P., 1983- (University Press of Florida, 2021)
"Presenting examples from the fields of critical race studies, cultural resource management, digital archaeology, environmental studies, and heritage studies, this volume demonstrates the many different ways archaeology can be used to contest social injustice"--